TIKTOK GENERATION MEETS ENGLISH EDUCATION: RETHINKING LEARNING MODELS FOR MODERN STUDENTS - Ni Made Rya Maharani; I Putu Andre Suhardiana; Igna Wijaya Mahardika (Cangkal : Jurnal Ilmu Sosial Dan Humaniora, 2026)
The rapid advancement of digital technology has transformed the characteristics, learning preferences, and educational expectations of contemporary learners. This study aims to examine the implications of the emergence of the TikTok Generation for English language education and to explore the necessity of rethinking learning models for modern students. Employing a qualitative library research design, the study systematically reviewed scholarly literature on digital learning, social media-based education, TikTok-mediated learning, microlearning, and English language teaching. Data were collected from peer-reviewed journal articles, books, conference proceedings, and academic reports published between 2018 and 2025 and analyzed using qualitative content analysis and thematic synthesis. The findings reveal that contemporary learners demonstrate high levels of digital literacy, preference for visual and interactive content, demand for personalized learning experiences, and engagement in collaborative online learning environments. Traditional English language learning models characterized by teacher-centered instruction, textbook dependence, and limited technology integration are increasingly inadequate in addressing these characteristics. The study further identifies TikTok as a catalyst for educational innovation through its support for microlearning, authentic communication, learner-generated content, and collaborative learning practices. The study concludes that English language education should adopt more learner-centered, technology-enhanced, flexible, and interactive learning models to remain relevant in the digital era. Such transformation can contribute to the development of communicative competence, creativity, critical thinking, and digital literacy among modern learners.